COVID19 PANDEMIC AND PREGNANCY - Yu. V. Prosvyetov; Yu. M. Bessarabov; S. S. Barinov; A. Yu. Gusarova (Сучасні медичні технології)
In a COVID19 pandemic, pregnant women become infected no more frequently than the general population. COVID19 in pregnant women is associated with a higher risk of caesarean section. Pregnant women with COVID19 who are obese, have high blood pressure, or a combination of two or more conditions are at risk for more severe disease and longer hospital stays.